Pendekatan Uji Statistik Peminatan Prajurit Marinir dalam Mengikuti Pendidikan Brevet Intai Amfibi (Taifib) - Pamuharsi Pamuharsi; Untung Purnomo; Istin Marlena Dewi (Rekayasa, 2022)
According to the results of the brevet monitoring that has been carried out by the Department of Applied Psychology, the Subdiscipline of Applied Psychology on students of career NCO education and Private Private Career education, it is indicated that at this time the alumni of career NCO education and career Private Enlisted Officers lacked interest in attending education. This brevet can be seen from the number of soldiers who follow the brevet monitoring with the number of registrants when the opportunity is opened to take brevet education. This decline in interest occurred in all brevet education, and one of them was Taifib brevet education. Psychological aspects have a strong influence on interest, therefore researchers feel it is important to conduct research on the psychological aspects of the Marines Self Concept (X1) on interest in attending taifib brevet education and psychological aspects of emotion regulation (X2) on marine soldiers' interest in attending education taifib brevet (Y). The research method used in this study is a quantitative research method using the Classical Assumption Test. The results showed that Self Concept (X1) and emotion regulation (X2) simultaneously had no significant effect on the interest of marines in attending taifib brevet education (Y). attending taifib brevet education that self-concept and emotional regulation only affect 17% of marines' interest in attending taifib brevet education. Meanwhile, 83% of marines' interest in attending taifib brevet education is more influenced by other variables outside the study.